Participatory Leadership in Madrasah Governance: Exploring Practices, Paradoxes, and Power Relations in Islamic Secondary Education - Hasbiyallah Hasbiyallah; Mochammad Rifky Alfauzy; Ahmad Fawaiz Hakim; Muhammad Sabiq Alfaruq; Ani Sumarni (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Participatory leadership in madrasah governance has become increasingly significant in response to growing demands for transparency, accountability, and collaboration in Islamic education. This study aims to examine and analyze participatory leadership practices in a Madrasah Tsanawiyah, focusing on mechanisms of participation, teachers’ interpretations, and the distribution of roles and responsibilities. Employing a qualitative case study design, data were collected through in-depth interviews, non-participant observations, and document analysis involving the principal, vice principals, and teachers engaged in madrasah management. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that participatory leadership is primarily enacted through deliberative forums that function as formal spaces for teacher involvement while simultaneously serving as mechanisms of social legitimacy for institutional decisions, despite the persistence of centralized authority. Teacher participation in supervision and deliberation is experienced ambivalently, functioning both as a dialogical process of professional development and as a source of professional pressure. Furthermore, the distribution of roles reflects organizational trust and collaboration but also generates role ambiguity due to limited clarity of authority and resource support. These findings suggest that participatory leadership in madrasah governance is best understood as a dynamic and context-dependent spectrum of social practices.